Estudo da estabilidade termodinâmica dos cristais de L-Fenilalanil-L-Alanina Diidratada e Ácido Eicosanóico (forma C) - Cordeiro, Adrya Jakellyne Paulo (2024)
In this study, the crystals of L-Phenylalanyl-L-Alanine dihydrate (Phe-Ala·2H₂O) and eicosanoic acid (C-form), more commonly known as arachidic acid (AA), were analyzed under ambient conditions and with varying thermodynamic parameters. The research was structured in two parts: the first addresses the hydrophobic dipeptide Phe-Ala·2H₂O, while the second investigates the saturated fatty acid (AA). Regarding Phe-Ala·2H₂O, scanning electron microscopy, X-ray diffraction, differential scanning calorimetry, infrared and Raman spectra, as well as computational calculations, were performed, from which the assignment of Raman and infrared vibrational modes was made. Furthermore, Raman spectroscopy experiments under pressure were conducted up to approximately 7 GPa. Changes in the Raman spectra were observed, which were interpreted as tubular structure deformation, and the set of modifications was associated with conformational changes in the ranges of 2.6 to 3.0 GPa and 5.0 to 5.1 GPa, as well as a structural phase transition between 0.4 and 1.0 GPa. A Raman spectroscopy experiment with temperature variation up to 473 K evidenced two transition intervals: 343 to 353 K and 393 to 403 K. Above 343 K, partial water loss from the structure was observed, causing the breaking of some hydrogen bonds and the consequent introduction of disorder into the crystal. For AA, scanning electron microscopy, X-ray diffraction, infrared, and Raman spectroscopies under ambient conditions were conducted, with the assignment of normal vibrational modes based on previous studies of materials from the same molecular family. A Raman spectroscopy experiment under pressure up to 8.1 GPa indicated two possible conformational changes in the ranges of 0.4 to 0.9 GPa and 2.7 to 3.2 GPa, and a possible structural phase transition initiated at 4.9 GPa, suggesting a loss of symmetry. Computational calculations with pressure variation were also performed and corroborated the results obtained through Raman spectroscopy. A Raman spectroscopy experiment with temperature variation from 300 to 10 K revealed significant changes in the intervals of 190 to 140 K and 100 to 40 K, indicating a conformational change and a structural transition, respectively. Comparisons of these results with those of other fatty acids, providing insights into the problem presented here, are also provided.